Effect of the quality of life therapy intervention on the burden of the family caregivers of addicts - Zahra Karimi; Nasrin Rezaee; Mansour Shakiba; Ali Navidian (Tehran University of Medical Sciences, 2019)
Background & Aim: Substance use as a crisis and a long-term chronic disorder can lead to psychological burden and reduce the quality of life of family caregivers. The aim of this study was to determine the effect of the quality of life therapy intervention on the burden of the family caregivers of addicts. Methods & Materials: This is a clinical trial. The research population included all the family caregivers of the recovering addicts, admitted to Baharan psychiatric hospital in Zahedan in 2018. The samples were 80 people who were randomly divided into either intervention or control group. Caregivers in the intervention group received eight sessions of group counseling based on the quality of life therapy and on the basis of the determined content, every other day. Before the intervention and eight weeks after the intervention, the data were collected using the Zarit burden questionnaire and were analyzed by statistical tests through the SPSS software version 21. Results: Before the intervention, there was no significant difference in the mean score of burden between the two groups (P=0.25). After the intervention, the mean score of family caregiver burden in the intervention group (40.10±12.92) was significantly lower than in the control group (46.80±13.58) (P<0.01). Conclusion: The quality of life therapy intervention in this study had a positive and significant effect on reducing the burden of family caregivers of addicts. Therefore, it is recommended that healthcare providers use this counseling approach along with addiction treatment programs to improve the psychological well-being of family caregivers. Clinical trial registry: IRCT20160924029954N11